A Non-Synonymous Coding Variant (L616F) in the TLR5 Gene Is Potentially Associated with Crohn's Disease and Influences Responses to Bacterial Flagellin - Sheridan, Jared (Public Library of Science, 2013)
BACKGROUND AND OBJECTIVES: Although numerous studies have implicated TLR5, or its ligands, bacterial flagellins, in the pathogenesis of Crohn's disease (CD), genome-wide association studies (GWAS) have not reported associations with the TLR5 gene. We aimed to examine potential CD-associated TLR5 variants and assess whether they modified inflammatory responses to bacterial flagellins. METHODS AND PRINCIPAL RESULTS: A two-stage study was carried out. In stage 1, we genotyped tagging single-nucleotide polymorphisms (tag-SNPs) in the TLR5 gene in a sample of CD cases (<20 years of age, N = 566) and controls (N = 536). Single SNP and haplotype analysis was carried out. In Stage 2, we assessed the functional significance of potential CD-associated variant(s) vis-à-vis effects on the inflammatory response to bacterial flagellin using HEK293T cells. We observed marginal association between a non-synonymous coding SNP rs5744174 (p = 0.05) and CD. Associations between SNP rs851139 that is in high linkage disequilibrium (LD) with SNP rs5744174 were also suggested (p = 0.07). Haplotype analysis revealed that a 3 marker haplotype was significantly associated with CD (p = 0.01). Functional studies showed that the risk allele (616F) (corresponding to the C allele of SNP rs5744174) conferred significantly greater production of CCL20 in response to a range of flagellin doses than the comparator allele (616L). CONCLUSIONS: Our findings suggest that a non-synonymous coding variation in the TLR5 gene may confer modest susceptibility for CD.